Review Buku Tradisi Pesantren Studi Tentang Pandangan Hidup Kyai Penulis Zamaksyari Dhofier - Munjahid (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2022)
The Pesantren Tradition Book is a translation of Zamakhsyari Dhofier's dissertation which was compiled to obtain a doctorate degree in Social Anthropology at the Australian National University (ANU), Canberra, Australia in 1980, and is the result of field research on two pesantren, namely Pesantren Tebuireng in Jombang and Pesantren Tegalsari. in Salatiga which was conducted from September 1977 to August 1978 and was funded by The Australian Development Assistance Bureau (ADAB).